Influência do relevo e uso do solo na variação local dos atributos climáticos na região central do estado de Minas Gerais - Heli Cassio Monteiro (2023)
The study area called “central region of the state of Minas Gerais” comprises a total of 102,309 km², which represents 17.4% of the state's territory. There are 519 municipalities throughout the surveyed area, with a population of 14.497.621,00 inhabitants. The locations that form part of the central region are widely diverse in terms of land use and vegetation cover. Furthermore, these areas present economic activities ranging from mineral extraction to agriculture, industry, commerce and services. Deforestation and changes in land use related to urban, industrial, agricultural and mining expansion affect the dynamics of the atmosphere at the microclimatic, topoclimatic and local climate levels. The reading of the interactivity between society and nature witnessed at these scales in the central region of the state of Minas Gerais points to possible environmental prognoses and future solutions that would support a less disharmonious relationship between the social and natural system in the area. The general objective of this research is to analyze the variations in climatic elements (temperature, relative air humidity, and precipitation) in the study area, considering historical data between 1961 and 2021, from a multiscale perspective (local-regional) and interaction of the surface with the lower troposphere. The specific objectives of the research are: to produce a mapping of local climatic units, together with transects (vertical representation) representative of weather types and to generate a classification of weather types supported by temporal sequences that demonstrate the climatic rhythm for the basin areas, identifying atmospheric systems (regional scale) and temporal developments on a local scale (weather types). Atmospheric systems and their relationship with phenomena such as El Niño and La Niña have considerable influences on the climate composition presented by the meteorological stations researched. The latitudinal arrangement associated with topography are two of the main foundations for defining the types of weather and also, in the climate classification of the central region of Minas Gerais. The concomitance between tropicality and the transience of climates in the state of Minas Gerais, especially in its central portion, presents hot and rainy climate types in the summer and with considerable temperature variations in the winter, generally colder and drier. The types of weather defined in the research are the result of a process of scalar decomposition and systemic analysis of the climate and its factors.